The impact of the COVID‐19 pandemic on the mental health and well‐being of children and young people - Cowie, Helen; Myers, Carrie‐Anne (Children & society, 2021)
The COVID‐19 pandemic has had an enormous impact across the world. In this discussion paper, we examine the effect that lockdown has had on the mental health and well‐being of children and young people. We write from a UK perspective in the light of the international evidence. Many of the discussion points raised resonate globally. We discuss how these issues can be dealt with and set out potential solutions as we emerge from this global crisis.